Replika . Dolny Śląsk miesięcznik niezależny, no. 11, 1983 - Norwid, Cyprian, Kamil; Konarski, Feliks; Wałęsa, Lech; Falicki, Paweł (Agencja Wydawnicza Solidarności Walczącej, 1983)
Print run: 1200-2000 copies